Democracy is a good thing [ essays on politics, society, and culture in contemporary China - Yu, Keping (The Thornton Center Chinese thinkers series, 2009)
"Presents selections of works of Yu Keping, a Chinese intellectual and figure in official think tanks, on politics and democracy that reveal the ongoing debates in Chinese political and intellectual circles on democratic reform and where China's politic